Sea ice : physics and remote sensing - Shokr, Mohammed; Sinha, Nirmal (Washington, D.C. : American Geophysical Union ; Hoboken, New Jersey : John Wiley & Sons, 2015)
1. Sea ice physical, dielectric and radiometric properties 1.1 Sea ice phase diagram 1.2 Sea ice growth under different oceanographic and atmospheric conditions 1.3 Thickness-based ice types 1.4 Physical properties of sea ice 1.5 Dielectric properties of ice type 1.5.1 Measurements of complex dielectric constant 1.5.2 Modeling complex dielectric constant 1.6 Radiometric properties of ice types 2. Ice Crystalline Structure 2.1 Hexagonal structure and birefringence of ice 2.2 Thin ice section double microtoming technique 2.3 Sea ice fabric diagram 2.4 Categories of ice crystalline struc.
4.1.3. Basic Terms and Definitions4.2. Morphology of Ice; 4.2.1. Form of Ice Crystals; 4.2.2. Miller Indices for Hexagonal Ice; 4.2.3. Growth Direction of Ice Crystals; 4.2.4. Ice Density in Relation to Crystalline Structure; 4.3. Structure- and Texture-Based Classification of Natural Ice; 4.3.1. Freshwater Ice Classification of Michel and Ramseier; 4.3.2. Extending Crystallographic Classification of Freshwater Ice to Sea Ice; 4.3.3. Crystallographic Classes of Natural Ice; 4.3.4. Stereographical Projection (Fabric Diagram) of Natural Polycrystalline Ice
Includes bibliographical references (p. 507-534) and index.
Print version record.
Keywords: Sea ice -- Remote sensing; Sea ice -- Arctic regions; Sea ice; Sea ice -- Remote sensing; SCIENCE / Earth Sciences / Geography; SCIENCE / Earth Sciences / Geology; Ice mechanics; Salinity; Sea ice; Arctic Regions; Electronic books; Electronic books